Kesepian dan Depresi pada Lansia: Systematic Literature Review - Latifah Rahmi. R; Nathania Aprillya Mirdansyah Waoma; Ratu Natasya At-Taqqiyah; Rahmadianti Aulia (CV. ITTC INDONESIA, 2026)
Loneliness is one of the most common psychological problems experienced by older adults due to biological, psychological, and social changes associated with aging. This condition may negatively affect mental health, particularly by increasing the risk of depression. This study aimed to analyze the relationship between loneliness and depression among older adults using a Systematic Literature Review (SLR) approach. Articles were collected from Google Scholar and ScienceDirect databases published between 2016 and 2026 using the keywords loneliness, depression, and elderly. The article selection process followed the PRISMA guidelines. Of the 209 articles identified, 20 met the inclusion criteria and were included in the review. The findings indicated that most studies reported a positive and significant relationship between loneliness and depression among older adults. Loneliness was not only associated with higher levels of depressive symptoms but also identified as a major risk factor predicting future depression. Social isolation, loss of a spouse, and limited social interaction were found to strengthen this relationship. In contrast, social support, social connectedness, resilience, and participation in social activities served as protective factors against depression. These findings suggest that enhancing social support and social participation is essential for maintaining mental health and improving the quality of life of older adults.